2011
DOI: 10.1007/s12275-011-1063-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Acinetobacter baumannii 19606 and 1656-2 with Acanthamoeba castellanii

Abstract: Acinetobacter baumannii is virtually avirulent for healthy people but maintains a high virulence among critically ill patients or immuno-compromised individuals. The ability of A. baumannii to adhere to cells and persist on surfaces as biofilms could be central to its pathogenicity. In the present study, we compared the virulence of the A. baumannii 1656-2 clinical strain, which is able to form a thick biofilm, with the virulence of the A. baumannii type strain (ATCC 19606(T)). Acanthamoeba castellanii, a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…1B-D ). Previous studies showed that A. baumannii invasion of mammalian cells can ultimately induce host cell death (Choi et al, 2005; Kim et al, 2008; Smani et al, 2011; Tamang et al, 2011). To determine whether the bacterium similarly killed alveolar cells, we measured the release of LDH, an indicator of host cell death, following infection (Pei and Ficht, 2004; Pei et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…1B-D ). Previous studies showed that A. baumannii invasion of mammalian cells can ultimately induce host cell death (Choi et al, 2005; Kim et al, 2008; Smani et al, 2011; Tamang et al, 2011). To determine whether the bacterium similarly killed alveolar cells, we measured the release of LDH, an indicator of host cell death, following infection (Pei and Ficht, 2004; Pei et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…However, certain bacteria especially pathogenic bacteria have developed strategies to escape the killing mechanisms of Acanthamoeba and instead use the amoeba as a Trojan horse or reservoir for their own benefit [12,13]. Some bacteria protect themselves from preying amoeba by secreting soluble anti- Acanthamoeba substances in their medium [14-16] or directly injecting such substances into Acanthamoeba through the type III secretory system [15]. These findings suggest that Acanthamoeba and Bacteria encounter each other in the environment routinely.…”
Section: Resultsmentioning
confidence: 99%
“…have shown that pathogenic bacteria, but not those who are weakly or not pathogenic, can survive within A. castellanii cysts 16 . The ability of R. ornithinolytica to grow and cause cytopathic effect in A. castellanii seems to be correlated with its virulence 14 , 15 . We demonstrated that strain Marseille-P1025 was not only able to survive within amoebae but could also multiply more efficiently than the control strain and kill amoebae, supporting its virulent behavior.…”
Section: Discussionmentioning
confidence: 99%